Analisis Pembelajaran IPAS Menggunakan Model Problem Based Learning Di Kelas IV - Upita Ayu Widayanti; Isnaini Wahyuningrum; Arum Emilia Salikha; Maulida Nurkhaliza; Afifah Fatin Pratiwi; Sri Suwartini (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This study aims to analyze how to apply the problem based learning model in IPAS learning in grade IV and the constraints during learning. This type of research uses descriptive qualitative methods. The instruments used are observation, interviews, and documentation. The subjects of this study were homeroom teachers in grade 4 and grade 4 students with a total of 11 students, of which there were 6 boys and 5 girls in MI Ma'arif Drono for the 2023/2024 school year. The results of this study can be concluded, IPAS learning has certain characteristics and has an impact on educators and students in implementing IPAS learning because students are given understanding by analyzing problems regarding events that occur around humans, the environment and social conditions. This research is expected to provide the latest innovations regarding the problem based learning model which is a guideline in carrying out learning steps from preliminary activities to final activities in IPAS learning.